Cognitive analysis of Dental Surgeons' profiles on Instagram, based on the Anco-Redes model (Research, Society and Development, 2024)
Instagram is a prominent communication tool in the health sector, whether providing guidance on disease prevention or highlighting the work of professionals. In this sense, the study aimed to carry out a cognitive analysis of the profiles of dental surgeons on the Instagram network, understanding the need to pay attention to the dissemination of information about oral health and frequently accessed content. Quantitative and qualitative aspects were addressed, using the AnCo-Redes model, which allows an analysis of the interconnections and dynamics present in the Instagram network, expanding the understanding of the phenomenon studied. The content with the most prominent points was represented by: “procedure results” and “botox”. The term "dental procedure results" is frequent and relevant in relation to interactions on Instagram, representing 15.03% of nodes (or terms) and 15.02% of connections (or edges) on the network. The term "botox" was the second most recurrent, displaying 134 edges, 9.36% of the total, indicating a number of connections and significant participation in the robustness of the system. However, other topics of great importance for maintaining oral health were minimally addressed, showing that the use of Instagram by dental surgeons, as a resource for disseminating information, is not aimed at preventing oral diseases. Both presented a high degree of centrality when compared to the other nodes in the network, indicating that they play a prominent role on Instagram. The analysis identified that the most discussed dental content is related to aesthetic dentistry, justified by its potential to generate greater reach, engagement, visualization and centrality in the studied network.